WTAP promotes lipopolysaccharides-induced ferroptosis in human renal tubular epithelial cells by regulating ACSL4 m6A methylation - ZHANG Qin; TANG Qing; CHEN Bingyang (Yixue xinzhi zazhi, 2025)
Objective To investigate the role of Wilms' tumor 1-associating protein (WTAP) in lipopolysaccharide (LPS) induced ferroptosis in human renal tubular epithelial cells (HK-2) and its molecular mechanism.Methods Expression differences of WTAP and long chain acyl-CoA synthetase 4 (ACSL4) between acute kidney injury tissues and healthy control tissues were analyzed based on the GEO database. HK-2 cells were treated with 10 μg/mL LPS, and cell viability, cell apoptosis, reactive oxygen species (ROS), glutathione (GSH) and Fe2+ contents were measured. The expression levels of GPX4, ACSL4, and WTAP were evaluated by Western blotting, and MeRIP-qPCR was used to examine the m6A methylation level of ACSL4. A cellular model of WTAP gene disruption with ACSL4 overexpression was constructed using si-RNA and plasmids to detect the binding of ACSL4 to WTAP and the effect of ACSL4 overexpression on cell injury and ferroptosis.Results Compared with the healthy control group, the expression levels of WTAP and ACSL4 were significantly upregulated in acute kidney injury tissues. LPS treatment reduces HK-2 cell viability, increases apoptosis, reduces GSH content, increases the level of Fe2+ and ROS, reduces GPX4 expression, upregulates the protein expression of WTAP and ACSL4, and the m6A methylation level of ACSL4 in a time-dependent manner. After knocking down of WTAP, the protein expression and m6A methylation level of ACSL4 were decreased, the binding between ACSL4 and WTAP weakened, and the mRNA stability of ACSL4 was reduced. Compared with the LPS group, the LPS+si-WTAP group showed increased cell viability, decreased apoptosis, and reduced ferroptosis levels, and overexpression of ACSL4 reversed the protective effects of si-WTAP on LPS-induced HK-2 cells.Conclusion WTAP upregulates the expression of ACSL4 by promoting m6A methylation of ACSL4, thereby aggravating LPS-induced ferroptosis and cell injury in human renal tubular epithelial cells.